Electronic and optical modulation of pine tree-like nanostructures of gallium nitride - Saleem, Umar (2022)
We present the synthesis and characterization of gallium nitride (GaN) pine tree-like nanostructures (PTLNs) grown by low-pressure chemical vapor deposition. A high yield of PTLNs is densely arranged with each PTLN having a typical length of 15.46 ± 3.38 μm. From Raman spectroscopy, we observe anE2Hpeak at 570 ± 6 cm-1which is the primary characteristic of wurtzite. X-ray and ultraviolet photoemission spectroscopy reveal that the electronic structures of GaN PTLNs indicate an n-type character, while the work function and valence band maximum are determined to be 3.30 ± 0.05 and 3.85 ± 0.08 eV, respectively. We confirm the electronic nature of our structure from the current-voltage characteristics exhibiting rectifying behavior. Density functional theory calculations of GaN PTLNs modeled by germanium-doped GaN nanowires are consistent with our experimental findings. To summarize, the energy-band diagram is presented for the future of GaN PTLNs in the optoelectronic and sensing applications.